G255(P) When can we say enough is enough?. (May 2019) - Desai, D; Whittley, C; Herath, D
Abstract : A patient previously reviewed in the clinic for incontinence lasting over two years with normal investigations, presented acutely to the assessment unit with inability to pass urine for 24 hours. Detailed examination revealed only a palpable bladder. Subsequently she passed urine without need for catheterisation and was discharged. Two days later, she presented again with urinary retention. Urinalysis was normal and an ultrasound showed an enlarged bladder. This time she voided (600 ml volume) only after catheterisation. Trimethoprim was prescribed for a presumed urinary infection. She did not pass urine for the next 28 hours and experienced excruciating abdominal pain necessitating admission (for five days) and re-catheterisation (passing 1000 ml of urine). Extensive investigations including MRI head, spine and pelvis were normal. There was no evidence of constipation. Persistent retention necessitated a tertiary urology referral; urodynamic studies, cystoscopy and repeat MRI found no cause. Over the next month she attended hospital four more times, usually requiring overnight stays and catheterisation each time due to retention of urine in excess of 600 ml. After the last visit, the patient was discharged home with a catheter in situ until the symptoms resolved 4 weeks later. Altogether this patient had six hospital admissions, reviews by urologists and paediatricians, several urinary microscopies, culture and sensitivities and blood tests. No pathological cause was ever found. It was later revealed that the patient suffered from anxiety relating to three main factors; her parents' recent divorce, recurrent nightmares about her father attacking her with a knife and bullying at school. The focus of management then shifted to psychological intervention which improved acute retention for a short duration; only for her to present with episodic diarrhoea and vomiting. Investigations and gastroenterology referral failed to reveal any pathology. This case demonstrates psychogenic causes for urinary retention rarely seen in children and the strain applied by varied presenting complaints on already stretched acute services. It poses the question of where paediatricians should draw the line on when to hand over care to psychiatrists and psychologists.